Overweight is associated with low fitness level among regional government employees in Denpasar City - Puspitasari, Kadek Dina; Widarini, Ni Putu (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: Time spent on sedentary work is a potential risk factor of nutritional problems among employees, which could lead to a low level of fitness. This study aims to determine the correlation between nutritional status with fitness level among government employees of Denpasar City. Methods: This is an analytic observational study with a cross-sectional design. The samples of this study are 285 government employees in Denpasar City who had taken a physical fitness measurement test using the Rockport method and complete demographic data. Data on fitness level, nutritional status, age, gender, and pulse rate were included in the analysis using a multinomial logistic regression test. Results:The median age of employees are 47 years old and slightly more females (51.6%) than males. More than half of the employees had a low level of fitness (50.9%) and most were overweight (47%). The overweight group was 4.11 times more likely to have a low fitness level than the healthy weight group (RRR=4.11; 95%CI: 1.03-16.32). Conclusion: There is a significant relationship between nutritional status and fitness level after gender, age, and pulse rate were controlled. Therefore, it is necessary to maintain a normal nutritional status to maintain or enhance individual fitness level by routinely following regular sports activities that have been programmed and do stretching in between working hours.